Influência de desordens metabólicas no desenvolvimento de lesões periapicais em ratos : efeito da terapia antioxidante - Wolle, Carlos Frederico Brilhante (2012)
The objective of this study was to evaluate the influence of two models of metabolic disorders, cardiomyopathy and type 2 diabetes, on periapical lesions in rats, and to evaluate the possible benefits of treatment with the antioxidant compound tempol in these experimental models. Initially, to assess the effects of tempol in periapical lesions of rats with doxorubicin-induced cardiomyopathy, 40 Male Wistar rats were divided into four groups: (i) naïve rats orally treated with saline solution (10 ml/kg) during 21 days after periapical lesion induction); (ii) naïve rats treated with tempol (30 and 50 mg/kg, during 21 days after periapical lesion induction), by oral pathway; (iii) rats with doxorubicin-induced cardiomyopathy treated with saline solution by oral route (10 ml/kg, from day 3 to day 21 after initiating treatment with doxorubicin); and (iv) rats with doxorubicin-induced cardiomyopathy orally treated with tempol (30 and 50 mg/kg, , from day 3 to day 21 after initiating treatment with doxorubicin).Body weight was recorded throughout the experimental period. Periapical lesions were induced on the first right mandibular molar tooth. Following 21 days of apical periodontitis induction, the animals were euthanized, and the mandibles were collected for radiographic and histological analysis. Samples of livers and hearts were removed for determination of free radicals. The oral administration of tempol (50 mg/kg) was able to significantly prevent the establishment of periapical lesions in either control animals or in rats submitted to the model of doxorubicin-induced cardiomyopathy, according to radiographic and histological evaluation. Nevertheless, the protective effects of tempol were virtually greater in control animals, in comparison to doxorubicin-treated rats, as indicated by histological inflammatory assessment. This might be related to the increased production of free radicals under cardiomyopathy. Treatment with tempol was able to reverse significant weight loss induced by doxorubicin, although the reduction of catalase activity was not significantly altered in the liver or heart.Subsequently, we investigated the development of periapical lesions in rats with type 2 diabetes. In this part of the study, 20 Male Wistar rats were used; they received tap water (N= 5) or a 20%-glucose solution (N = 15) during nine weeks. At the sixth week, periapical lesions were induced on the first mandibular molars, and the animals were subdivided into four groups. The subgroup (i) was composed by non-diabetic rats orally receiving saline solution (10 ml/kg). Glucose-fed insulin resistant rats were divided into the following subgroups: (ii) saline-treated animals (10 ml/kg, by oral route); animals orally treated with tempol (iii) 50 mg/kg; or (iv) 100 mg/kg. The body weight was monitored thoroughly. Following 21 days of apical periodontitis induction, the animals were euthanized, and the mandibles were collected for radiographic and histological analysis. The livers were removed to determine free radicals and the blood plasma was used to measure insulin levels. Type-2 diabetic rats displayed a significant decrease of body weight gain and a slight increase of insulin levels, allied to reduced levels of the antioxidant components catalase and GSH; these alterations were virtually reversed by tempol (100 mg/kg).The extent and cellularity of periapical lesions in glucose-fed type 2 diabetic rats was similar to that seen in control rats. However, administration of tempol, even at a dose of 100 mg/kg, was no able to change the periapical lesions in diabetic rats, suggesting that systemic therapy with tempol was ineffective in rats submitted to a high-glucose diet. In conclusion, treatment with tempol showed beneficial systemic effects on apical periodontitis in both control animals and in rats with doxorubicin-elicited cardiomyopathy, at the dose of 50 mg/kg. However, despite affecting other parameters related to diabetes, tempol (for up to 100 mg/kg) failed to improve the outcome of endodontic lesions in type-2 diabetic animals. This data might be useful to support the treatment planning for patients with metabolic disorders looking for endodontic treatment. Other therapeutic strategies should be 16 evaluated in the same experimental models, including the use of intracanal dressings containing tempol, as well as the association with hypoglycemic agents, such as metformin